Trainees’ perceptions on learning environment based on the level of training in a pediatric training program in Indonesia - Rina Triasih; Felisia Ang; Weda Kusuma; Gandes Retni Rahayu (Indonesian Pediatric Society, 2022)
Background Learning environment in a pediatric specialist training program is complex and may influence trainees’ performance and achievement. We evaluated the trainees’ perception on learning environment and compared it between levels of the training. Methods We conducted a cross-sectional study to pediatric trainees in Pediatric Specialist Training Program at Universitas Gadjah Mada, Yogyakarta, Indonesia in May 2019. The data was collected online using the Postgraduate Hospital Educational Environment Measure (PHEEM) questionnaire, which was translated into Indonesian language and was self-completed by the trainees. Results All (136) trainees, which consisted of 35 (25.7%) junior, 44 (32.3%) middle, and 57 (42%) senior levels, completed the survey. The mean total score of PHEEM for all trainees was 108.10 (+ 17.03), which was not different between levels of the trainees. The mean scores for the role of autonomy, teaching, and social support were not different between levels of training either. Nevertheless, the junior scored less than the middle and senior trainees for questions on performing inappropriate tasks. Conclusion The learning environment of the pediatric training program in our setting was perceived good but improvement was required. There was no difference in perception of learning environment based on the level of the training.